Influence of La2O3 Additive Content on the Phase Stability, Sintering and Microstructure of 8 MOL% Y2O3 Stabilized Cubic Zirconia (8YSZ) Ceramic Used for Solid Oxide Fuel Cell Applications - (:unkn) unknown (John Wiley and Sons, 2012)
The effect of La2O3 content up to 15 wt% on phase stability, sintering and microstructure of cubic zirconia (8YSZ) was investigated. XRD results showed that the specimens containing up to 15 wt% La2O3 were composed of only cubic structure. Also, the specimens doped up to 5 wt% La2O3 revealed no La2O3 peaks, indicating that La2O3 was completely solubilized in the cubic structure. However, when > 5 wt% La2O3 was added, the peak of La2Zr2O7 compound emerged, showing that the overdoped La2O3 was not solubilized in the 8YSZ matrix. The lattice parameter of the 8YSZ slightly decreased with the increasing La2O3 content up to 1 wt% but further increase in the La2O3 amount resulted in an increased lattice parameter. The comparison of grain size of the 8YSZ specimens with various La2O3 content showed that grain size slightly increased with the increasing La2C3 content up to 1 wt% but further increase in the La2O3 amount resulted in a decreased grain size. © 2012 The Minerals, Metals, & Materials Society. All rights reserved.
Keywords: Cubic zirconia; La2O3; La2Zr2O7; Microstructural investigation; Sintering